Labor force participation during COVID-19 and risk of depression: a Danish register study. (18th November 2022) - Hellmann, Sophie S; Møller, Sanne P; Ersbøll, Annette K; Santini, Ziggi I; Nielsen, Maj Britt D; Grønbæk, Morten K; Ekholm, Ola; Thygesen, Lau C
Abstract: Background: COVID-19 caused economic insecurity for businesses and their employees. Understanding effects of changes in labor force participation on depression risk during economic recession is fundamental for early diagnosis. The study evaluates if changes in labor force participation are associated with depression risk during COVID-19 in Denmark. Methods: A register-based longitudinal study of Danes aged 25–67 years without depression 2 years prior to baseline defined as February 2020. An eight-level categorical variable on stable or changing labor force participation was defined from monthly employment percentage gradients in the Danish Register-based Evaluation and Marginalization Database from February 2020. The cohort was followed until 31 December 2020 for depressions overall and mild-, moderate- and severe depression. Sex-stratified cox regression models with hazard ratios (HR) and 95% confidence intervals (95% CI) were performed accounting for important confounders. Results: In total, 1 619 240 (50.3%) men of mean age 45.6 years and 1 598 587 (49.7%) women of mean age 45.9 years were included. Becoming unemployed implied an increased HR of depression in men (HR 2.02; 95% CI 1.94–2.10) and women (2.19; 2.12–2.26) compared to a steady-state full-time employment. Being outside the labor force or employed part-time implied an elevated HR in men (3.02; 2.82–3.23 and 2.41; 2.35–2.48) and women (3.13; 2.30–3.31 and 2.30; 2.26–2.35), respectively, compared to a steady-state full-time employment. Conclusions: Changes in labor force participation were associated with higher risk of depression relative to a steady-state full-time employment particularly among individuals with low labor force participation during COVID-19.